Coupled semiconductor nanocomposite g-C3N4/TiO2 with enhanced visible light photocatalytic activity. (April 2016) - Mohini, R.; Lakshminarasimhan, N.
Graphical abstract: Highlights: g-C3 N4 /TiO2 nanocomposites by in situ growth of TiO2 nanoparticles over 2D g-C3 N4 Enhanced visible light photocatalytic activity of g-C3 N4 in nanocomposite Efficient separation of photogenerated charge carriers in nanocomposite Abstract: The visible light photocatalytic activity of graphitic carbon nitride, g-C3 N4, can be enhanced by coupling with other semiconductors. In this work, mesoporous TiO2 nanoparticles were grown over g-C3 N4 sheets resulting in the coupled nanocomposite photocatalyst. The morphological analyses using FE-SEM, TEM and AFM revealed the uniform deposition of TiO2 on g-C3 N4 sheet. The visible light photocatalytic activity of g-C3 N4 and g-C3 N4 /TiO2 composites were tested by methyl orange (MO) dye degradation and Cr(VI) reduction. The results revealed an enhancement in the visible light photocatalytic activity of g-C3 N4 when it was coupled with TiO2 in the nanocomposite. Mesoporous TiO2 nanoparticles deposited over g-C3 N4 provides the necessary large surface for the adsorption of the pollutant molecules. The enhanced visible light photocatalytic activity of g-C3 N4 in the nanocomposite is due to the high surface area and efficient photogenerated charge carrier separation in the nanocomposite as evidenced in photoluminescence (PL) results.